Effect of off-center finned absorber tube and nanoparticle shape on the performance of two-fluid parabolic solar collector containing nanofluid: An application of artificial neural network. (December 2021) - Alnaqi, Abdulwahab A.; Alsarraf, Jalal; Al-Rashed, Abdullah A.A.A.
Abstract: The present paper aims to evaluate the effect of using an off-center finned absorber tube on the efficiency of a two-fluid parabolic trough solar collector (PTC) filled with a nanofluid (NF) with different nanoparticle (NP) shapes and diameters. Simulations are conducted for different Reynolds numbers and solid volume fractions (SVFs) using both the single-phase method (SPM) and two-phase method (TPM) with Fluent software. It was found that the energy efficiency of the two-fluid PTC is higher than the single-fluid PTC. In addition, the outcomes revealed that the energy efficiency of the PTC elevates with using an off-center finned absorber tube, increasing the Reynolds number and decreasing the SVF. Moreover, it was reported that the use of TPM instead of the SPM entails a rise in the energy efficiency of the PTC. Among the studied cases, the highest energy efficiency was equal to 58.9%, which belonged to the two-fluid PTC with off-center finned absorber tube filled with the NF with SVF of 1% containing spherical NPS with diameter of 40 nm at Reynolds number of 5000. Finally, the artificial neural network was employed to assess the sensitivity of energy efficiency to the Reynolds number.